Composting yard as a sustainable alternative for the treatment of organic waste generated by port activities - Oliveira, Anaís França de Matos; Ferreira, Laiê Rodrigues Porto; Martins, Gabriel Afonso; Corrêa, Luciara Bilhalva; Corrêa, Érico Kunde (Brazilian Journal of Production Engineering, 2025)
Seaports are important to the Brazilian economy due to their capacity to transport large volumes of cargo. The port of Santarém, located in the state of Pará, handles millions of tons of goods annually, with soybeans being one of the region’s main products. Ports generate organic waste that poses health risks to workers and the local population. Composting is a controlled microbiological decomposition process that results in an organic compound, which can be used as fertilizer. This study proposes the implementation of a composting yard to treat organic waste from port activities. The composting windrows were sized to meet the technical criteria required for the installation of a Sorting and Composting Plant, as established in standard NBR 13896/97. As a result, this study demonstrated the necessary area for the yard and the recommended number of windrows, aiming to meet the demand for organic waste generated by port operations in the coming years. The project presented, in the end, a predicted functionality for up to 20 years, taking into account the increase in waste generation and the consequent reduction in costs for its disposal.